2021
DOI: 10.1021/acs.macromol.1c00559
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Copolymerization with Limonene and β-Pinene: New Bio-Based Polyolefins Prepared by Coordination Polymerization

Abstract: Synthesis of new semicrystalline polymers by copolymerization of ethylene with R-(+)-limonene (Lim) and β-pinene (Pin) has been demonstrated by using phenoxide-modified half-titanocene catalysts, Cp’TiCl2(O-2,6- i Pr2-4-RC6H2) (Cp’ = cyclopentadienyl; R = H and SiEt3), in the presence of a methylaluminoxane (MAO) cocatalyst. High-molecular-weight poly­(ethylene-co-Lim)­s (M n = 4.09–16.4 × 104) were prepared by using the (1,2,4-Me3C5H2)­TiCl2(O-2,6- i Pr2C6H3)–MAO catalyst system. Synthesis of high-molecular-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…Table summarizes the results for ethylene copolymerizations with myrcene (My) using various half-titanocene ( 1 – 4 , Chart )–MAO catalyst systems. The phenoxide- or ketimide-modified half-titanocenes shown in Chart , Cp′TiCl 2 (O-2,6- i Pr 2 -4-RC 6 H 2 ) [R = H, Cp′ = Cp* ( 1 ), t BuC 5 H 4 ( 3 ); R = SiEt 3 , Cp′ = Cp* ( 2 )] and CpTiCl 2 (N = C t Bu 2 ) ( 4 ), have been chosen in this study because these catalysts demonstrated efficient comonomer incorporations in the ethylene copolymerizations with sterically encumbered olefins, , cyclic olefins, and aromatic vinyl monomers. , An AlMe 3 -free MAO white solid, which was prepared from the commercially available MAO sample [8.9 wt % (Al) toluene solution, see the Experimental Section] by removing toluene and AlMe 3 in vacuo , , , was used as the cocatalyst. The results by the ordinary linked-amide half-titanocene, [Me 2 Si­(C 5 Me 4 )­(N t Bu)]­TiCl 2 ( 5 ), , and the metallocene catalyst, Cp 2 ZrCl 2 ( 6 ), conducted under the same conditions are also placed for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table summarizes the results for ethylene copolymerizations with myrcene (My) using various half-titanocene ( 1 – 4 , Chart )–MAO catalyst systems. The phenoxide- or ketimide-modified half-titanocenes shown in Chart , Cp′TiCl 2 (O-2,6- i Pr 2 -4-RC 6 H 2 ) [R = H, Cp′ = Cp* ( 1 ), t BuC 5 H 4 ( 3 ); R = SiEt 3 , Cp′ = Cp* ( 2 )] and CpTiCl 2 (N = C t Bu 2 ) ( 4 ), have been chosen in this study because these catalysts demonstrated efficient comonomer incorporations in the ethylene copolymerizations with sterically encumbered olefins, , cyclic olefins, and aromatic vinyl monomers. , An AlMe 3 -free MAO white solid, which was prepared from the commercially available MAO sample [8.9 wt % (Al) toluene solution, see the Experimental Section] by removing toluene and AlMe 3 in vacuo , , , was used as the cocatalyst. The results by the ordinary linked-amide half-titanocene, [Me 2 Si­(C 5 Me 4 )­(N t Bu)]­TiCl 2 ( 5 ), , and the metallocene catalyst, Cp 2 ZrCl 2 ( 6 ), conducted under the same conditions are also placed for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, resonances at 53 ppm (quaternary carbon confirmed by dept) and 46.5–49.5 ppm (tertiary carbon confirmed by dept) were observed. These resonances were apparently different from those considered by 1,2-, 2,1-, or 1,4-My insertion. , It also seems likely that resonances observed at 22–23 ppm (secondary carbon) could be ascribed to those corresponding to methylene carbon in a cyclopentane inserted unit observed in ethylene/cyclopentene copolymers with exclusive 1,2-cyclopentene insertion. We thus further explored the microstructural analysis of poly­(ethylene- co -My)­s and the polymer after hydrogenation by RhCl­(PPh 3 ) 3 (see the Experimental Section), including the dept analysis (Figure ). No significant differences in the M n , Đ ( M w / M n ) values and their thermal properties ( T m , T g ) in the resultant polymers (runs 17, 20, Table ) were observed before/after the hydrogenation (see the Experimental Section).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of interesting green material sourcing trends have gathered recent interest, including terpenes, neoligans, amino acids, sugars/carbohydrates, cellulose, silk, and others. Of great interest to us is the terpene limonene, which has been examined for 3D printing directly of the monomer using thiol–ene reactions, modified through thiol–ene chemistry before incorporation into thermoplastic polymers displaying performance/engineering plastic behaviors, and has even been selectively oxidized prior to synthesis of degradable polyesters and polycarbonates. However, polymerization of limonene without modification has been characterized by low yields and oligomeric products. A second terpene of interest is β-myrcene, which possesses a linear structure containing three alkenes and has been utilized as a comonomer with petrochemicals such as styrene as well as with itaconic acid, farnesene, or ocimene. Modification of myrcene commonly focuses on functionalizing with reactive groups such as acrylates or similar derivatives to increase reactivity and better control over the resultant molecular weights. However, a key characteristic of the β-myrcene-containing polymers is the low elastic modulus and high strain at break, with block copolymers particularly demonstrating this behavior …”
Section: Introductionmentioning
confidence: 99%